(untitled) (Journal of Advanced Veterinary and Animal Research, 2023)
Objective: This study was conducted to evaluate the effect of composting on the count of Salmonella spp., Clostridium perfringens, and New Castle virus (NDV) isolated from broilers’ litter. Moreover, to verify the impact of compost thermal stress on the expression of thermal genes harbored in the isolated bacteria. Materials and Methods: The prevalence of enteric aerobic and anaerobic infections by Salmonella spp., C. perfringens, and viral infections by NDV were investigated in litter samples collected from 100 broiler flocks by conventional methods and polymerase chain reaction. Results: The samples were positive for Salmonella spp., C. perfringens, and NDV, with prevalence rates of 60%, 55%, and 30%, respectively. An experiment to study the effect of compost on the microbiological quality of litter was applied using five compost heaps with an initial average count of Salmonella typhimurium (3.2 × 105 CFU CFU/gm), C. perfringens (6.4 × 105 CFU/gm), and an average titer NDV (105.5 embryo infectious dose50/gm). The microbiological count of heaps after 15 days of composting revealed a reduction in the count of S. typhimurium and C. perfringens by 4 log10 CFU/gm and 3 log10 CFU/gm, respectively. Moreover, the hemagglutinating test revealed no detection of NDV after 15 days of composting. A high degree of downregulation of expression of the thermal genes, dnaK in S. typhimurium isolates and cpe gene in C. perfringens isolates, was detected by quantitative reverse transcription PCR. Conclusion: The reduction of pathogen counts, the simplicity, and the low cost associated with composting for only 15 days advocate the recommendation for raising awareness of composting as a routine biosecurity measure to prevent the spreading of infection and promote its safe use in agribusiness. J. Adv. Vet. Anim. Res., 10(3): 458–468, September 2023 http://doi.org/10.5455/javar.2023.j699